Maternal Near Miss (Severe Morbidity) at Sisaket Hospital - Wanchai Wianwiset (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
Objective:To study the incidence of maternal near miss cases (severe morbidity), their near miss events and obstetric outcomes at Sisaket Hospital.Materials and Methods: This prospective cross-sectional study was conducted between October 1st, 2010 and September 30th, 2011. We recriuted all women over 28 weeks of gestation who gave birth, all deaths of pregnant women and fetuses during pregnancy, childbirth or within seven days of termination of pregnancy and all maternal near miss cases. The maternal and neonatal data were obtained from medical records. Data were analyzed and presented as odds ratio with 95% confidence intervals.Results:Sample were 4,503 deliveries with 260 near miss cases and 288 near miss events which no maternal death occurred. The incidence of maternal near miss cases was 57.7 per 1,000 deliveries. Pregnancy - induced hypertension was the most common near miss event (34.3 per 1,000 deliveries). Multiparity, gestational age < 38 weeks and without true labor were significantly increased in the near miss cases. Cesarean delivery, birth weight between 1,500- 2,499 grams, Apgar score at 5 minutes < 7, admission to NICU were the more common obstetric outcomes in the near miss cases comparing with the non near miss cases.Conclusion:The incidence of maternal near miss cases was 57.7 per 1,000 deliveries. Pregnancy - induced hypertension was the most common near miss event (34.3 per 1,000 deliveries).